Complementing biological inventories through open data in a semiautomated method - Cabrera-Cruz, Sergio A.; Aguilar-López, José Luis; Villegas-Patraca, Rafael (Revista de Biología Tropical, 2024)
Introduction: Surveys are the best way to document the biological richness of any given place, but efforts to do so can be limited. We asked whether the species richness documented through fieldwork can be complemented with open data from digital platforms. Objective: To analyze whether species occurrence data available in the Global Biodiversity Information Facility (GBIF) can complement species lists reported in the literature obtained through fieldwork. Methods: We compared bird species lists published in peer-reviewed articles and those generated with information from GBIF for the same study areas using the Sorensen dissimilarity index (βsor) and its two components (turnover βsim and nestedness βsne). Results: GBIF reported more species (n = 26-232) than 14 of the 24 lists consulted, but fewer (n = 12-114) than the other 10. The sum of species documented by both sources represents an increase between 1.6 and 464 % compared with the number of species in the articles alone, showing the potential for complementation between both sources. βsor ranged between 0.15-1, showing differences between all species lists. In no instance βsim = 0 or βsne = 1, indicating that one source of information always listed species absent in the other source and that species nestedness between sources of information was never total. We provide R code that can be adapted to download and clean GBIF data for any biological group and place. Conclusion: Species occurrences available in GBIF can complement the information collected in the field but this, in turn, can also complement the records of GBIF, so we highlight the importance of continuing documenting the biological richness through fieldwork, especially in little-explored areas.